Characterization of Arabidopsis Post-Glycosylphosphatidylinositol Attachment to Proteins Phospholipase 3 Like Genes - Bernat-Silvestre, Cesar; Ma, Yingxuan; Johnson, Kim; Ferrando, Alejandro; Aniento, Fernando; Marcote, María Jesús (Frontiers in Plant Science, 2022)
Lipid remodeling of Glycosylphosphatidylinositol (GPI) anchors is required for their maturation and may influence the localization and function of GPI-anchored proteins (GPI-APs). Maturation of GPI-anchors is well characterized in animals and fungi but very little is known about this process in plants. In yeast, the GPI-lipid remodeling occurs entirely at the ER and is initiated by the remodeling enzyme Bst1p (Post-Glycosylphosphatidylinositol Attachment to Proteins inositol deacylase 1 -PGAP1- in mammals and Arabidopsis). Next, the remodeling enzyme Per1p (Post-Glycosylphosphatidylinositol Attachment to Proteins phospholipase 3 -PGAP3- in mammals) removes a short, unsaturated fatty acid of phosphatidylinositol (PI) that it is replaced with a very long-chain saturated fatty acid or ceramide to complete lipid remodeling. In mammals, lipid remodeling starts at the ER and is completed at the Golgi apparatus. Studies of the Arabidopsis PGAP1 gene showed that the lipid remodeling of the GPI anchor is critical for the final localization of GPI-APs. Here we characterized loss-of-function mutants of Arabidopsis Per1/PGAP3 like genes (AtPGAP3A and AtPGAP3B). Our results suggest that PGAP3A function is required for the efficient transport of GPI-anchored proteins from the ER to the plasma membrane/cell wall. In addition, loss of function of PGAP3A increases susceptibility to salt and osmotic stresses that may be due to the altered localization of GPI-APs in this mutant. Furthermore, PGAP3B complements a yeast strain lacking PER1 gene suggesting that PGAP3B and Per1p are functional orthologues. Finally, subcellular localization studies suggest that PGAP3A and PGAP3B cycle between the ER and the Golgi apparatus.